2017
DOI: 10.29262/ram.v64i1.233
|View full text |Cite
|
Sign up to set email alerts
|

Seguridad de la inmunoterapia subcutánea con extractos tirosinados de ácaros de polvo doméstico en pacientes con enfermedad alérgica

Abstract: The frequency of systemic reactions with subcutaneous immunotherapy with Dermatophagoides farinae, Dermatophagoides pteronyssinus and Blomia tropicalis tyrosine-adsorbed extracts was similar to that reported with other extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…That study showed that immunological potency inducing allergen-specific IgG4 antibody was the highest in aqueous HDM extract and the lowest in tyrosine-adsorbed HDM extract. Another previous study reported a very low incidence of SR (0.35%; 45 of 12,546 injections) during the conventional schedule of SCIT with tyrosine-adsorbed HDM extract in patients with allergic diseases 20. Therefore, in this study, we used a tyrosine-adsorbed HDM extract for UR-SCIT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…That study showed that immunological potency inducing allergen-specific IgG4 antibody was the highest in aqueous HDM extract and the lowest in tyrosine-adsorbed HDM extract. Another previous study reported a very low incidence of SR (0.35%; 45 of 12,546 injections) during the conventional schedule of SCIT with tyrosine-adsorbed HDM extract in patients with allergic diseases 20. Therefore, in this study, we used a tyrosine-adsorbed HDM extract for UR-SCIT.…”
Section: Discussionmentioning
confidence: 98%
“…The severity and incidence of SR during SCIT are dependent on the potency of the allergen extract 12. We searched for a HDM preparation for SCIT with a relatively low allergenic potency and low incidence of SR but having reasonable evidence of clinical efficacy in patients with AD and AR 61420. A previous study compared the immunological potencies of 3 kinds of commercially available HDM extracts for SCIT (aluminum hydroxide-adsorbed HDM extract, tyrosine-adsorbed HDM extract, and aqueous HDM extract) in patients with allergic diseases 21.…”
Section: Discussionmentioning
confidence: 99%
“…10 A fi nal del seguimiento y 12546 dosis se registraron 45 reacciones adversas sistémicas (tasa de reacción 0.35 % por 100 inyecciones), para una tasa de incidencia de 5.8 % No se produjeron reacciones fatales. 11 Con el extracto de ácaros polimerizados, 622 pacientes tuvieron una tasa de reacción de 1.06 por 100 inyecciones, 93.1 % grados 1 y 2. 12 De acuerdo con estos tres estudios no hubo diferencias estadísticamente signifi cativas en la frecuencia o severidad de las reacciones entre estos dos extractos de ácaros modifi cados de inmunoterapia subcutánea (ITSC).…”
Section: Seguridadunclassified